The vital blend of clinical competence and compassion: How patients experience person-centred care. Issue 2 (6th May 2016) - Sharp, Sandra; McAllister, Margaret; Broadbent, Marc
Abstract : Background : Person-centred care is a policy priority for health services seeking to assure the public they provide safe, high-quality care, in keeping with rising consumer expectations. However, study of person-centred care rarely includes acute-care patients' perspectives. Methodology : In 2013, semi-structured interviews were held with 10 former patients of an Australian regional health service and examined via thematic analysis to understand patients' experiences of nursing care, interpret findings in the context of person-centred care principles and identify ways to enhance and support compassionate, person-centred care in everyday nursing practice. Results : Clinically competent care, delivered compassionately through a positive nurse–patient relationship, resulted in personal, emotional or spiritual responses that were the catalyst for patient empowerment and participation in care, and a positive outlook toward recovery. Implications for practice : Nurses wishing to implement person-centred care need to recognise the importance of prioritising human connection and compassion in conjunction with clinical competence.